Écriture Feminine in the Narration Level of Jeanette Winterson’s The Powerbook - Nisa’ul Fithri Mardani Shihab (TEKNOSASTIK, 2017)
This writing examines the narration level in Jeanette Winterson’s novel The Powerbook (2000) by focusing on the concept of écriture feminine, referring to the structure and the form of narration. Jeanette Winterson is one of woman writers in English literature whose works indicate a form of écriture feminine as a counter discourse for phallogocentrism. Winterson’s works in the narration level exhibit the difference from the conventional narration forms. In The Powerbook, écriture feminine in the narration level is shown in the form of fragmented narration that comes in three different forms, namely: narcissistic narrative, public narration and demythologizing history. The result of the research points out that the narration form of the novel is a resistance toward phallogocentrism by demonstrating women’s writing that manifests the way women make sense of their world.